How do you factor and solve #-x^2-2x+3 = 0#?
Taken you through the process step by step
First of all I am going to make a deliberate mistake.
So in error write:
Lets consider just the
Because we have a negative
We now need
So the factorisation is
x = 1, and x = -3
Since a + b + c = 0, use shortcut.
The 2 real roots are:
x = 1 , and
Rule of Shortcut.
If a + b + c = 0, The 2 real roots are: x = 1, and
If a - b + c = 0, The 2 real roots are: x = -1, and
Remember this shortcut. It will save you a lot of time and effort.